INVESTIGATION OF THE ANHARMONIC CORRELATION EFFECTS BY DEBYE MODEL IN X-RAY ABSORPTION FINE STRUCTURE SPECTRA–APPLICATION TO A TWO-COMPONENT ALLOY - Nguyễn Bá Đức; Vũ Quang Thọ; Trịnh Phi Hiệp; Nguyễn Văn Nghĩa; Phạm Thị Minh Hạnh; Vũ Thị Thanh Hà (Tạp chí Khoa học Đại học Đà Lạt)
The displacement correlation function in extended X-ray absorption fine structure spectra has been determined based on the Debye-Waller factor. The anharmonic correlated Debye model and the harmonic Debye model have been used to build analytical expressions of mean square displacement, mean square relative displacement, and correlation function dependence on temperature and doping ratio. The thermodynamic quantities have been calculated based on the effective anharmonic potential, including the interaction of absorbing and scattering atoms with their nearest neighbors in an atom cluster. The analytical expressions have been applied to face-centered cubic crystals and their alloys. Numerical results for crystalline copper (Cu) and copper-silver alloys (CuAg) of 72% and 50% ratios agree well with experimental values and other studies. The study has contributed to our knowledge of the thermodynamic properties of 50:50 CuAg doped alloy at low temperatures.